Micropower Impulse Radar: A Novel Technology for Rapid, Real-Time Detection of Pneumothorax - Phillip D. Levy; Tracey Wielinski; Alan Greszler (Emergency Medicine International)
Pneumothorax detection in emergency situations must be rapid and at the point of care. Current standards for detection of a pneumothorax are supine chest X-rays, ultrasound, and CT scans. Unfortunately these tools and the personnel necessary for their facile utilization may not be readily available in acute circumstances, particularly those which occur in the pre-hospital setting. The decision to treat therefore, is often made without adequate information. In this report, we describe a novel hand-held device that utilizes Micropower Impulse Radar to reliably detect the presence of a pneumothorax. The technology employs ultra wide band pulses over a frequency range of 500 MHz to 6 GHz and a proprietary algorithm analyzes return echoes to determine if a pneumothorax is present with no user interpretation required. The device has been evaluated in both trauma and surgical environments with sensitivity of 93% and specificity of 85%. It is has the CE Mark and is available for sale in Europe. Post market studies are planned starting in May of 2011. Clinical studies to support the FDA submission will be completed in the first quarter of 2012.